2015
DOI: 10.1590/0034-737x201562010007
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis: a tool in the study of post-harvest diseases in peaches

Abstract: RESUMO Análise de sobrevivência como ferramenta no estudo de doenças na pós-colheita de pêssegosA análise de sobrevivência é aplicada quando o tempo até a ocorrência de um evento for o objeto de interesse. Em doenças de plantas, dados dessa natureza são rotineiramente coletados, embora aplicações do método sejam pouco comuns. O objetivo deste trabalho foi utilizar dois estudos de doenças em pós-colheita de pêssegos, considerando-se safras conjuntamente e a existência de efeito aleatório, compartilhado por frut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…These values were underestimates because the Kaplan-Meier nonparametric estimation method was restricted to the largest time to symptom expression while in reality there were censored individuals. Nesi et al, (2015) also reported having encountered limitations of the Kaplan-Meier test when analysing post-harvest diseases of peaches.…”
Section: Censored and Un-censored Datamentioning
confidence: 99%
See 3 more Smart Citations
“…These values were underestimates because the Kaplan-Meier nonparametric estimation method was restricted to the largest time to symptom expression while in reality there were censored individuals. Nesi et al, (2015) also reported having encountered limitations of the Kaplan-Meier test when analysing post-harvest diseases of peaches.…”
Section: Censored and Un-censored Datamentioning
confidence: 99%
“…These results confirm the nonparametric results that the two types of crosses belong to different distributions. The likelihood ratio tests (Giroux et al, 2016) compared parametric fits of the simpler, or restricted, models with the more complicated, or unrestricted Generalized gamma model (Nesi et al, 2015). The hypothesis tested was equality of restricted and unrestricted models.…”
Section: Parametric Testsmentioning
confidence: 99%
See 2 more Smart Citations